Ultrahigh-concentration cerium ion activated borosilicate scintillation glass rich in Gd2O3 as well as preparation method and application thereof
By enriching Gd2O3 in the borosilicate system and using ultra-high concentration CeO2 doping, combined with an appropriate amount of Al2O3 or Lu2O3 to replace Gd2O3, scintillation glass with high density, high light yield and short attenuation time was prepared, and the current solution was solved In some technology, the problem of flickering glass is difficult to have high density, high gloss yield and fast attenuation at the same time, which has expanded its application in high-energy physics experiments.
Patent Information
- Application Number
- CN202411174843.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing cerium ion-doped borosilicate scintillation glass is difficult to have the characteristics of high density, high gloss yield and fast attenuation, which limits its application in high-energy physics experiments.
By enriching Gd2O3 in the borosilicate system, using ultra-high concentration CeO2 doping, combining an appropriate amount of Al2O3 or Lu2O3 to replace Gd2O3, and performing full mixing, melting, mold casting and precision annealing at high temperature, it is prepared. High-performance scintillation glass with a density exceeding 7.0g/cm3.
The high density, high light yield and fast attenuation time of scintillation glass are achieved, ensuring its important application value in nuclear radiation detection, high-energy physical experiments, X-ray medical imaging, neutron detection and other fields.
Smart Images

Figure CN119118507A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of luminescent materials, and relates to scintillation glass materials, preparation methods and applications thereof, and in particular to an ultra-high concentration cerium ion-activated Gd2O3-rich borosilicate scintillation glass, and a preparation method and application thereof. Background Art
[0002] Scintillator detectors are one of the most important radiation detectors and are often used in high-energy physics experiments, nuclear radiation detection, nuclear medicine, and industrial flaw detection. Scintillator materials can convert high-energy particles or rays into visible light and are optical functional materials. Scintillator crystals are the most widely studied and applied scintillators, such as Bi4Ge3O 12 (BGO), CeF3, PbWO4 (PWO), etc. However, scintillating crystals have the disadvantages of complex preparation process, long growth cycle, high cost and difficulty in producing large-size single crystals. In particular, traditional crystal growth technology is difficult to ensure ultra-high concentration and uniform distribution of doped ions, and thus cannot achieve the optimization of optical properties of materials, which greatly limits its application.
[0003] With the rapid development of high-energy physics, the performance requirements for scintillating materials have become increasingly stringent, which in turn has promoted the high-quality research of scintillating materials. In order to achieve accurate measurements of particles such as Higgs, W and bosons, the Chinese particle physics community proposed the construction of a circular electron-positron collider (CEPC). CEPC needs to cover a wide range of solid angles, excellent particle identification capabilities, accurate measurement of particle energy-momentum, high-precision collision vertex resolution, injection resolution and flavor marking. For the hadron calorimeter system of CEPC, the effective supply of batch scintillating materials is one of the important guarantees. Scintillating glass is a priority target for hadron calorimeters because of its advantages such as easy adjustment of chemical composition, good optical uniformity, easy realization of large size and simple preparation method. However, hadron calorimeters require scintillating glass to have high density, visible optical yield, fast decay time and strong radiation resistance. On the other hand, the Compact Muon Coil (CMS) of the Large Hadron Collider (LHC) at the European Organization for Nuclear Research (CERN) is also considering the design of using scintillating glass to replace the original scintillating crystals, and the Large Electron Ion Collider (EIC) in the United States is also actively promoting the development of scintillating glass calorimeter technology. Therefore, scintillating glass is likely to be the most important scintillator in the next generation of high-energy physics experiments, and is also an important research hotspot for scintillating materials.
[0004] High density is one of the important performance indicators of scintillating materials in high-energy physics experiments. High-density scintillators have a shorter radiation length and better blocking ability for high-energy particles. They can improve the energy resolution of detectors and facilitate the compact design of large scientific equipment. However, scintillating glass has a contradiction between density and light yield that is difficult to coordinate, such as "high density but low light yield" or "low density but high light yield". At present, the density of glass is 3.5-8.5g / cm 3 For example, the invention patent with the publication number CN1087066A and the name of "High-density, radiation-resistant, fast-scintillation inorganic glass" discloses that the density of the glass with PbO and Bi2O3 as the main components exceeds 8.0g / cm 3 scintillating glass, but the glass component contains a large amount of PbO, which seriously pollutes the environment, thus limiting its practical application. For example, the invention patent with the publication number CN101913767A and the name "Rare earth doped fluorine oxytellurate scintillating glass and its preparation method" discloses a high-density scintillating glass with TeO2, PbF2, BaF2 and Gd2O3 as the main components and rare earth as the luminescence center. The scintillating glass still contains highly toxic PbF2 and other fluorides, which seriously pollute the environment, thus limiting the promotion and application of this type of scintillating glass. For example, the invention patent with the publication number CN 114409252A and the name "A boron-free high-density gadolinium lutetium germanate glass and its preparation" discloses a high-density gadolinium lutetium germanate glass with a density of more than 6.0g / cm 3 Germanate scintillating glass, but the components GeO2, Lu2O3 and Ga2O3 in the glass are expensive and have high melting temperatures, which is not conducive to the promotion and application of this type of scintillating glass. For example, the patent publication number is CN 115611514 A, and the name is "A Ce 3+ The invention patent of "GaB-doped Gd-doped scintillating glass and its preparation method and application" discloses a glass with a density higher than 6.0g / cm 3 However, the Ga2O3 component in the glass is expensive, and its CeO2 doping concentration is lower than 4 mol%, which is not conducive to reducing the scintillation decay time.
[0005] Borosilicate system is often used as scintillating glass matrix due to its strong rare earth solubility, good optical properties, stable physical and chemical properties, and abundant raw materials. Low-valent cerium ions are often used as luminescence centers because they allow 5d-4f transitions and can produce decay times of nanoseconds. Therefore, cerium ion-doped borosilicate glass is a very important scintillating material and has long been highly concerned by academia and industry. However, cerium ion luminescence is Ce 3+ Luminescence, the preparation of this type of scintillating glass requires the use of H2 / N2 mixed gas or CO gas to keep Ce in a low valence state 3+Luminescence, or by introducing different strong reducing components in air atmosphere to simplify the preparation process and reduce the cost of glass preparation. 3+ Two invention patents, "A method for preparing activated scintillating glass" (patent publication number CN104058578A) and "A colorless and transparent cerium-activated borosilicate scintillating glass and its preparation method" (publication number CN108249757A), both disclose a series of methods for preparing colorless and transparent cerium ion-activated scintillating glass in an air atmosphere, providing an important method for the synthesis of a series of low-valent cerium ion-doped scintillating glasses in an air atmosphere.
[0006] On the other hand, researchers have been working hard to optimize the scintillation performance of cerium ion-doped borosilicate glass. For example, the invention patent with the patent publication number CN114772922A, entitled "Scintillator glass for electromagnetic calorimeter and its preparation method, melting device and application", discloses a borosilicate scintillator glass doped with cerium dioxide (concentration less than 3 mol%), with a fluorescence decay time of 20-48ns and a maximum light yield of 770ph / MeV. For example, the Chinese patent CN110734223B discloses a lutetium-based silicate scintillator glass with a glass density of more than 6.5g / cm 3 , but its CeO2 doping concentration is lower than 2.0mol%, which is not conducive to the radiation resistance of the scintillating glass and does not reveal more scintillating properties. Due to its inherent amorphous complex structure, the rich types and numbers of defects inside the glass increase the complexity of the scintillation process and significantly deteriorate the scintillation performance of the glass. For example, the fluorescence decay time of the cerium ion doped scintillating glass (publication number CN114772922A) mentioned above is 20-48ns, but its scintillation time is close to 1000ns.
[0007] In summary, the currently reported cerium ion-doped borosilicate scintillating glass is difficult to simultaneously possess the characteristics of high density, high light yield, and fast attenuation. Summary of the invention
[0008] The purpose of this application is to prepare a nanostructured carbon nanotube with a density exceeding 7.0 g / cm2 by enriching (Gd, Lu)2O3 in a borosilicate system, focusing on three performance indicators closely related to practical application needs, namely high density, visible light yield and fast decay. 3 The high-performance scintillating glass is optimized by doping with ultra-high concentration CeO2 to achieve practical application purposes. To this end, this patent discloses an ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass and its preparation method and application.
[0009] In order to solve the above technical problems, this application provides the following technical solutions.
[0010] In the first aspect, the present application provides an ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass, characterized in that the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is prepared from the following raw material components by fully mixing, high-temperature melting, mold casting and precision annealing:
[0011] B2O3 10-35mol%
[0012] SiO2 10-35mol%
[0013] Gd2O3 0-70mol%
[0014] CeO2: 0-20 mol%;
[0015] The sum of the above components is 100 mol%.
[0016] In one embodiment of the first aspect, the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is made of the following raw material components:
[0017] B2O3 15-30mol%
[0018] SiO2 15-28mol%
[0019] Gd2O3 35-65mol%
[0020] CeO2: 5-15 mol%.
[0021] The sum of the above components is 100 mol%.
[0022] In one embodiment of the first aspect, at least a portion of the Gd2O3 is replaced by Al2O3 or Lu2O3.
[0023] In one embodiment of the first aspect, an appropriate amount of SiO2 component is replaced by one or more of reducing Si3N4, SiC, SiO or elemental Si; or an appropriate amount of B2O3 component is replaced by one or more of reducing BN, B4C or elemental B.
[0024] In one embodiment of the first aspect, the composition of the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is as follows: 20B2O3-20SiO2-30Gd2O3-15Gd2F6; 24B2O3-21SiO2-40Lu2O3-15Gd2F6; 19Gd2O3-15Gd2F6-1Al2O3-22B2O3-17.75SiO2-0.25Si3N4-1CeO2; 23B2O3-20SiO2-15Gd2F6-(40-x)Gd2O3-xLu2O3, wherein x=0, 10, 20, 30, or 40; 24B2O3-23SiO2-(37Gd-x)2O3-2x Al(OH)3-15Gd2F6, wherein x=0, 5, 10, or 15; or, 23B2O3-23SiO2-(39-x)Gd2O3-x CeO2-15Gd2F6, wherein x=1, 3, 5, 7, 9, 12, or 16.
[0025] In a second aspect, the present application provides a method for preparing the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass as described in the first aspect, characterized in that the preparation method comprises the following steps:
[0026] S1: accurately weighing various raw materials according to the components of the scintillating glass, and mixing all the raw materials uniformly to obtain uniformly mixed glass materials;
[0027] S2: Melting the uniformly mixed glass material into a glass melt at a melting temperature of 1000-1400° C. and keeping the temperature for 10-120 minutes after melting;
[0028] S3: After the glass melt is uniform, the temperature is lowered to the melting temperature of 100-200°C and clarified for 15-60 minutes to obtain clarified glass melt;
[0029] S4: pouring the clarified glass melt into a mold preheated to 350-550° C. for casting and then cooling naturally to form glass;
[0030] S5: subjecting the glass to a constant temperature precision annealing treatment to obtain the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass. The annealing conditions are: an annealing temperature of 450-700°C and an annealing time of 3-30 hours.
[0031] In one embodiment of the second aspect, the B2O3 component is introduced by boron oxide or boric acid; the SiO2 raw material is directly introduced by the SiO2 raw material; and the Gd2O3 and CeO2 rare earth compounds are introduced in the form of corresponding oxides, fluorides, carbonates or nitrates; Al2O3 or Lu2O3 replacing Gd2O3 can also be introduced in the form of corresponding oxides, fluorides, hydroxides, carbonates or nitrates; the purity of all raw materials is required to be analytically pure or above.
[0032] In one embodiment of the second aspect, the B2O3 component is 10 B2O3 is introduced, while Gd2O3 component is introduced through 155 Gd2O3 and / or 157 Gd2O3 is introduced.
[0033] In one embodiment of the second aspect, the working atmosphere during the preparation process is an air atmosphere.
[0034] In the third aspect, the present application provides an application of the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass as described in the first aspect, characterized in that the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is used to directly make a scintillating screen or a scintillating array, or is drawn into an optical fiber to make an optical fiber panel.
[0035] In a fourth aspect, the present application provides an application of the ultra-high concentration cerium ion-activated Gd2O3-rich borosilicate scintillating glass as described in the first aspect, characterized in that the ultra-high concentration cerium ion-activated Gd2O3-rich borosilicate scintillating glass is used for nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, industrial online detection and national security monitoring.
[0036] Compared with the prior art, the positive effect of the present invention is that the density of the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass described in this article is closely related to the melting temperature, the holding time, the type of crucible, etc. The density and luminescence performance of the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass can also be regulated by partially replacing Gd2O3 in the glass with Lu2O3 or Al2O3. The main advantage of the scintillating glass of the present invention is that it can achieve ultra-high concentration 5-15mol% doping of CeO2, the luminescence center, in the Gd2O3-rich borosilicate scintillating glass, while ensuring high density, and can also obtain a high light yield of 1300ph / MeV and a scintillation decay time of about 100ns; on the other hand, due to the inherent transparency of the glass, the preparation process is simple, the components are easy to adjust, and the characteristics of low cost and large volume can be achieved, so that it has important application value in the fields of nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, industrial online detection and national security monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a density comparison diagram of the scintillating glasses obtained in Examples 1-3;
[0038] Figure 2 This is a density comparison diagram of the scintillating glasses obtained in Examples 4-8;
[0039] Figure 3 This is a density comparison diagram of the scintillating glasses obtained in Examples 9-10;
[0040] Figure 4 This is a density comparison diagram of the scintillating glasses obtained in Examples 11-14;
[0041] Figure 5 This is a comparison chart of the luminous intensity of the scintillating glasses obtained in Examples 11-14;
[0042] Figure 6 The transmission spectra of the scintillating glass obtained in Examples 15-21;
[0043] Figure 7 is the gamma-ray energy spectrum of the scintillating glass obtained in Examples 15-21;
[0044] Figure 8 The gamma-ray excited scintillation attenuation diagram of the scintillation glass obtained in Examples 15-21;
[0045] Fig. 9 This is the gamma-ray energy spectrum of the scintillating glass obtained in Example 22;
[0046] Fig.10 This is the gamma-ray excited scintillation attenuation diagram of the scintillation glass obtained in Example 22. DETAILED DESCRIPTION
[0047] Unless otherwise indicated, implied from the context, or customary in the prior art, all parts and percentages in this application are based on weight, and the test and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application or publication referred to in this application are fully incorporated herein by reference, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, product and processing designs, polymers, comonomers, initiators or catalysts disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.
[0048] Numerical ranges in this application are approximate values, so unless otherwise specified, they may include numerical values outside the range. Numerical ranges include all numerical values from the lower limit to the upper limit increased by 1 unit, provided that there is an interval of at least 2 units between any lower value and any higher value. For example, if the recorded component, physical or other properties (such as molecular weight, melt index, etc.) are 100 to 1000, it means that all single values are clearly listed, such as 100, 101, 102, etc., and all sub-ranges, such as 100 to 166, 155 to 170, 198 to 200, etc. For a range containing a numerical value less than 1 or containing a fraction greater than 1 (such as 1.1, 1.5, etc.), 1 unit is appropriately regarded as 0.0001, 0.001, 0.01 or 0.1. For a range containing a single digit less than 10 (such as 1 to 5), 1 unit is usually regarded as 0.1. These are only specific examples of what is intended to be expressed, and all possible combinations of values between the lowest and highest values listed are considered to be clearly recorded in this application. It should also be noted that the terms "first", "second", etc. in this article do not limit the order of precedence, but are only used to distinguish substances with different structures.
[0049] When used with respect to chemical compounds, unless expressly specified otherwise, the singular includes all isomeric forms and vice versa (e.g., "hexane" includes all isomers of hexane, individually or collectively). In addition, nouns using "a," "an," or "the" also include their plural forms unless expressly specified otherwise.
[0050] The terms "comprising", "including", "having" and their derivatives do not exclude the presence of any other components, steps or processes, and are irrelevant to whether these other components, steps or processes are disclosed in this application. To eliminate any doubt, unless explicitly stated, all compositions using the terms "comprising", "including", or "having" in this application may include any additional additives, adjuvants or compounds. On the contrary, except for those necessary for operating performance, the term "essentially consisting of..." excludes any other components, steps or processes from the scope of any description of the term below. The term "consisting of..." does not include any components, steps or processes that are not specifically described or listed. Unless explicitly stated, the term "or" refers to the listed individual members or any combination thereof.
[0051] In a specific embodiment, the present invention provides an ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass, which is prepared by the following raw material components through a process of fully mixing, high-temperature melting, mold casting and precision annealing:
[0052] B2O3 10-35mol%
[0053] SiO2 10-35mol%
[0054] Gd2O3 0-70mol%
[0055] CeO2: 0-20mol%.
[0056] CeO2 is introduced as a rare earth luminescence center, and its doping amount can reach up to 20 mol%. The sum of the above components is 100 mol%.
[0057] In one embodiment, the formula of ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is preferably:
[0058] B2O3 15-30mol%
[0059] SiO2 15-28mol%
[0060] Gd2O3 35-65mol%
[0061] CeO2: 5-15 mol%.
[0062] The sum of the above components is 100 mol%.
[0063] In a specific embodiment, part of Gd2O3 can be replaced by Al2O3 or Lu2O3. This replacement is beneficial to further optimize the luminescent properties of the scintillating glass to achieve its specific application in different scenarios.
[0064] In one embodiment, the present application provides a method for preparing ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass, which specifically includes the following steps:
[0065] 1) Accurately weigh each raw material according to the composition of the scintillating glass, and mix all the raw materials evenly. The B2O3 raw material is introduced from boron oxide (B2O3) or boric acid (H3BO3); the SiO2 raw material is directly introduced from the SiO2 raw material; and the Gd2O3 and CeO2 rare earth compounds can be introduced in the form of corresponding oxides, fluorides, carbonates or nitrates; Al2O3 and Lu2O3 that replace Gd2O3 can also be introduced in the form of corresponding oxides, fluorides, hydroxides, carbonates or nitrates; the purity of all raw materials must be analytical grade or above;
[0066] 2) Then pour the mixed glass material into a platinum crucible, an alumina crucible, a graphite crucible or a quartz crucible to melt it into a glass melt, the melting temperature is 1000-1400°C, and the temperature is kept for 10-120 minutes after melting. The type of crucible, melting temperature and holding time are determined according to the specific conditions such as the glass composition and its introduction form;
[0067] 3) After the glass melt is uniform, cool it down to the melting temperature of 100-200℃ and clarify it for 15-60 minutes;
[0068] 4) pouring the above molten glass into a stainless steel mold or graphite mold preheated to 350-550°C for casting and then cooling naturally to form glass;
[0069] 5) placing the glass in a muffle furnace for constant temperature precision annealing treatment, the annealing conditions are: annealing temperature is 450-700° C., and annealing time is 3-30 hours;
[0070] 6) The above-mentioned scintillating glass is processed into the scintillating glass sample of the present invention after cutting, surface grinding and polishing.
[0071] In a specific embodiment, the working atmosphere is mainly carried out in an air atmosphere; this realization is attributed to the replacement of an appropriate amount of SiO2 raw material in the glass component by one or more of reducing Si3N4, SiC, SiO or elemental Si; or it is attributed to the replacement of an appropriate amount of B2O3 raw material in the glass component by one or more of reducing BN, B4C or elemental B. It should be pointed out that in the process of glass batching, by replacing an appropriate amount of SiO2 raw material in the glass by one or more of reducing Si3N4, SiC, SiO or elemental Si, or replacing an appropriate amount of B2O3 raw material in the glass by one or more of reducing BN, B4C or elemental B, it is ensured that the glass preparation conditions can be completed in the atmospheric atmosphere, which greatly simplifies the glass preparation process and reduces the glass preparation cost.
[0072] In one embodiment, the density of the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass can be between 5.0 and 7.1 g / cm2 depending on the glass composition and melting process. 3 The maximum light output is about 1300ph / MeV.
[0073] In a specific embodiment, in the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass of the present application, when the luminescent center CeO2 content exceeds 7 mol%, the scintillation time can be reduced to about 100ns; when the luminescent center CeO2 content exceeds 15 mol%, the scintillation time can be reduced to about 60ns. At the same time, the ultra-high concentration of cerium ions makes the scintillating glass have excellent radiation resistance, which can realize the practical application of the scintillating glass.
[0074] In a specific embodiment, in the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass of the present application, when the B2O3 component is 10 B2O3 is introduced, while Gd2O3 component is introduced through 155 Gd2O3 and (or) 157When Gd2O3 is introduced, the capture cross section of neutrons and scintillation glass can be greatly improved, so the improved scintillation glass can be used for neutron detection.
[0075] In another embodiment, the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass of the present application can be directly made into a scintillating screen or a scintillating array; it can also be further drawn into an optical fiber to make an optical fiber panel to improve its imaging resolution.
[0076] In another embodiment, the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass of the present application can be applied to nuclear radiation detection, high energy physics experiments, X-ray medical imaging, neutron detection, industrial online detection and national security monitoring.
[0077] Example
[0078] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Unless otherwise specified, the reagents and raw materials used can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0079] Examples 1-3
[0080] The Gd2O3-rich borosilicate scintillating glass matrix formula is 20B2O3-20SiO2-30Gd2O3-15Gd2F6.
[0081] Analytical pure silicon dioxide (SiO2), boric acid (H3BO3), gadolinium oxide (Gd2O3) with a purity of 99.99%, and gadolinium fluoride (GdF3) are weighed according to a stoichiometric ratio and mixed evenly to prepare a mixture. Partial substitution of GdF3 for Gd2O3 is beneficial to lowering the melting temperature of the glass.
[0082] The mixture was transferred into a covered corundum crucible and melted in an air atmosphere at temperatures of 1150°C, 1200°C and 1250°C for 30 minutes. The molten liquid was poured onto a steel plate preheated to 400°C for casting.
[0083] The prepared glass was annealed in a muffle furnace heated to 530°C for 200 minutes and then cooled to room temperature along with the furnace.
[0084] The annealed scintillating glass is cut and surface-polished to obtain the colorless, transparent, Gd2O3-rich borosilicate scintillating glass matrix.
[0085] The test results show that the melting temperature has a significant effect on the density of scintillating glass, and a lower melting temperature is beneficial to increasing the density of scintillating glass.
[0086] Table 1. Effect of different melting temperatures on the density of Gd2O3-rich borosilicate scintillating glass
[0087]
[0088]
[0089] Embodiment 4-8
[0090] The formula of the Gd2O3-rich borosilicate scintillating glass matrix is 23B2O3-20SiO2-15Gd2F6-(40-x)Gd2O3-xLu2O3 (x=0, 10, 20, 30, 40), where the increase in the x value indicates a higher content of Lu2O3 replacing Gd2O3.
[0091] Analytical pure silicon dioxide (SiO2), boric acid (H3BO3) and 99.99% pure gadolinium oxide (Gd2O3), lutetium oxide (Lu2O3) and gadolinium fluoride (GdF3) are weighed according to a stoichiometric ratio and mixed evenly to prepare a mixture. Partial substitution of GdF3 for Gd2O3 is beneficial to lowering the melting temperature of the glass.
[0092] The mixture was transferred into a covered corundum crucible and melted in an air atmosphere at a melting temperature of 1190°C for 30 minutes. The molten liquid was poured onto a steel plate preheated to 460°C for casting.
[0093] The prepared glass was annealed in a muffle furnace heated to 570°C for 200 minutes and then cooled to room temperature along with the furnace.
[0094] The annealed scintillating glass is cut and surface-polished to obtain the colorless, transparent, Gd2O3-rich borosilicate scintillating glass matrix.
[0095] The test results show that as the x value increases, that is, when the amount of Lu2O3 replacing Gd2O3 is higher, the density of the scintillating glass has a significant increasing trend, from 6.0386 g / cm2 before replacement (x=0) to 3 , increased to 6.8337 g / cm after complete substitution (x = 40) 3 On the other hand, as more Lu2O3 replaces Gd2O3, the fluorescence intensity of the scintillating glass increases from 5.70337×10 7 (arbitrary intensity), increased to half of the part (x = 20) 6.59545 × 10 7 (arbitrary intensity), the fluorescence intensity increased by 15.64%.
[0096] Table 2. Effect of different concentrations of Lu2O3 replacing Gd2O3 on the density and luminescence intensity of Gd2O3-rich borosilicate scintillating glass
[0097]
[0098]
[0099] Examples 9-10
[0100] The Gd2O3-rich borosilicate scintillating glass matrix formula is 24B2O3-21SiO2-40Lu2O3-15Gd2F6.
[0101] Analytical pure silicon dioxide (SiO2), boric acid (H3BO3), lutetium oxide (Lu2O3) with a purity of 99.99%, and gadolinium fluoride (GdF3) are weighed according to a stoichiometric ratio and mixed evenly to prepare a mixture. Partial substitution of GdF3 for Gd2O3 is beneficial to lowering the melting temperature of the glass.
[0102] The mixed materials were transferred into covered corundum crucibles and Pt gold crucibles respectively, and melted in air atmosphere at a melting temperature of 1175°C and a holding time of 45 minutes. The molten liquid was poured onto a steel plate preheated to 380°C for casting.
[0103] The prepared glass was annealed in a muffle furnace heated to 430°C, kept warm for 200 minutes, and then cooled to room temperature along with the furnace.
[0104] The annealed scintillating glass is cut and surface-polished to obtain the colorless, transparent, Gd2O3-rich borosilicate scintillating glass matrix.
[0105] The test results show that the density characteristics of Gd2O3-rich borosilicate scintillating glass are related to the type of melting crucible. When corundum crucible is selected, its density is 6.5438g / cm 3 If platinum crucible is used for melting, its density is 7.1376 g / cm under the same conditions. 3 , an increase of more than 10%.
[0106] Table 3. Effect of using a non-through crucible on the density of Gd2O3-rich borosilicate scintillating glass
[0107]
[0108] Examples 11-14
[0109] The formula of the Gd2O3-rich borosilicate scintillating glass activated with a fixed concentration of 1 mol% CeO2 is 24B2O3-23SiO2-(37Gd-x)2O3-2x Al(OH)3-15Gd2F6 (x=0, 5, 10, 15).
[0110] Analytical pure silicon dioxide (SiO2), boric acid (H3BO3), aluminum hydroxide (Al(OH)3), gadolinium oxide (Gd2O3) with a purity of 99.99%, and gadolinium fluoride (GdF3) are weighed according to a stoichiometric ratio as raw materials, mixed evenly, and prepared into a mixture. Partial substitution of Al(OH)3 for Gd2O3 is beneficial to reducing the viscosity of the glass.
[0111] The mixed materials were transferred into covered corundum crucibles and melted in air atmosphere at 1180℃ for 30 minutes. Then the temperature was lowered to 1030℃ for about 20 minutes and the molten liquid was poured onto a steel plate preheated to 380℃ for casting.
[0112] The prepared glass was annealed in a muffle furnace heated to 450°C for 200 minutes and then cooled to room temperature along with the furnace.
[0113] The annealed scintillating glass is cut and surface-polished to obtain the colorless, transparent, Gd2O3-rich borosilicate scintillating glass matrix.
[0114] The results show that as the value of x increases, that is, when the amount of Al(OH)3 gradually replaces Gd2O3, the density of the scintillating glass increases from 6.0494 g / cm2 before replacement (x=0) to 3 , reduced to 5.1652 g / cm after partial substitution (x = 15) 3 , but the glass density is still higher than 5.0g / cm 3 On the other hand, the integrated fluorescence intensity of the glass increases from 8097.7542 (x=0) before replacement to 12176.7708 (x=15) after partial replacement, and the integrated luminous intensity increases by 50%; in addition, the emission center wavelength of the glass blue shifts from 380nm before replacement (x=0) to 357nm after partial replacement (x=15), which is beneficial to the light output of the scintillating glass.
[0115] Table 4. Gd2O3-rich borosilicate scintillating glass after different Al(OH)3 substitutions for Gd2O3
[0116]
[0117]
[0118] Examples 15-21
[0119] The matrix formula of the Gd2O3-rich borosilicate scintillating glass activated by different concentrations of cerium ions is 23B2O3-23SiO2-(39-x)Gd2O3-x CeO2-15Gd2F6 (x=1, 3, 5, 7, 9, 12 and 16).
[0120] Analytical pure silicon dioxide (SiO2), boric acid (H3BO3), gadolinium oxide (Gd2O3) with a purity of 99.99%, and gadolinium fluoride (GdF3) are weighed according to a stoichiometric ratio and mixed evenly to prepare a mixture. Partial substitution of Al(OH)3 for Gd2O3 is beneficial to reducing the viscosity of the glass.
[0121] The mixed materials were transferred into covered corundum crucibles and melted in air atmosphere at 1180℃ for 30 minutes. Then the temperature was lowered to 1030℃ for about 20 minutes and the molten liquid was poured onto a steel plate preheated to 380℃ for casting.
[0122] The prepared glass was annealed in a muffle furnace heated to 450°C for 200 minutes and then cooled to room temperature along with the furnace.
[0123] The annealed scintillating glass is cut and surface-polished to obtain the colorless, transparent, Gd2O3-rich borosilicate scintillating glass matrix.
[0124] The results show that as the x value increases, that is, the doping concentration of the scintillating glass increases, the density of the low-concentration CeO2-doped scintillating glass (x=1) is 6.0494 g / cm 3 , better than high concentration CeO2 doped scintillating glass (x = 7) with a density of 5.9432 g / cm 3 and ultra-high concentration CeO2 doped scintillating glass (x=12) with a density of 5.9152 g / cm 3 . However, the scintillation light yield is significantly enhanced from 427ph / MeV of low-concentration CeO2-doped scintillating glass (x=1) to 842ph / MeV of high-concentration CeO2-doped scintillating glass (x=7) and 903ph / MeV of ultra-high-concentration CeO2-doped scintillating glass (x=12); the corresponding average scintillation decay time is significantly shortened from 922.77ns of low-concentration CeO2-doped scintillating glass (x=1) to 100.81ns of high-concentration CeO2-doped scintillating glass (x=7) and 76.42ns of ultra-high-concentration CeO2-doped scintillating glass (x=12). Moreover, it can be predicted that further increasing the CeO2 doping concentration can continue to optimize its light yield and scintillation decay time, thereby realizing its practical application value.
[0125] Table 5. Activation of Gd2O3-rich borosilicate scintillating glass by different CeO2 concentrations
[0126]
[0127]
[0128] Embodiment 22
[0129] The formula of Gd2O3-rich borosilicate scintillating glass activated with a fixed concentration of 1 mol% CeO2 is 19Gd2O3-15Gd2F6-1Al2O3-22B2O3-17.75SiO2-0.25Si3N4-1CeO2.
[0130] Analytical pure silicon dioxide (SiO2), silicon nitride (Si3N4), boric acid (H3BO3), aluminum oxide (Al2O3) and 99.99% pure gadolinium oxide (Gd2O3) and gadolinium fluoride (GdF3) are weighed according to a stoichiometric ratio and mixed evenly to prepare a mixture. Partial substitution of Al2O3 for Gd2O3 is beneficial to optimizing the light yield of the glass.
[0131] The mixed materials were transferred into covered corundum crucibles and melted in air atmosphere at 1180℃ for 30 minutes. Then the temperature was lowered to 1030℃ for about 20 minutes and the molten liquid was poured onto a steel plate preheated to 380℃ for casting.
[0132] The prepared glass was annealed in a muffle furnace heated to 450°C for 200 minutes and then cooled to room temperature along with the furnace.
[0133] The annealed scintillating glass is cut and surface-polished to obtain the colorless, transparent, Gd2O3-rich borosilicate scintillating glass matrix.
[0134] The results show that the light yield of the optimized scintillator glass is increased to nearly 1300ph / MeV.
[0135] Table 6. Luminescence properties of Gd2O3-rich borosilicate scintillating glasses doped with different CeO2 concentrations
[0136]
[0137] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.
Claims
1. An ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass, characterized in that: The ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is prepared from the following raw material components by fully mixing, high-temperature melting, mold casting and precision annealing: B2O3 10-35mol% SiO2 10-35mol% Gd2O3 0-70mol% CeO2: 0-20 mol%; The sum of the above components is 100 mol%.
2. The ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass according to claim 1, characterized in that: It is made from the following raw materials: B2O3 15-30mol% SiO2 15-28mol% Gd2O3 35-65mol% CeO2: 5-15 mol%. The sum of the above components is 100 mol%.
3. The ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass according to claim 1, characterized in that: At least a portion of the Gd2O3 is replaced by Al2O3 or Lu2O3; And / or, an appropriate amount of SiO2 component is replaced by one or more of reducing Si3N4, SiC, SiO or elemental Si; And / or, an appropriate amount of B2O3 component is replaced by one or more of reducing BN, B4C or elemental B.
4. The ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass according to claim 3, characterized in that: The components of the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass are as follows: 20B2O3-20SiO2-30Gd2O3-15Gd2F6; 24B2O3-21SiO2-40Lu2O3-15Gd2F6; 19Gd2O3-15Gd2F6-1Al2O3-22B2O3-17.75SiO2-0.25Si3N4-1CeO2; 23B2O3-20SiO2-15Gd2F6-(40-x)Gd2O3-xLu2O3, wherein x=0, 10, 20, 30, or 40; 24B2O3-23SiO2-(37Gd-x)2O3-2x Al(OH)3-15Gd2F6, wherein x=0, 5, 10, or 15; or, 23B2O3-23SiO2-(39-x)Gd2O3-x CeO2-15Gd2F6, wherein x=1, 3, 5, 7, 9, 12, or 16.
5. The method for preparing ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: accurately weighing various raw materials according to the components of the scintillating glass, and mixing all the raw materials uniformly to obtain uniformly mixed glass materials; S2: Melting the uniformly mixed glass material into a glass melt at a melting temperature of 1000-1400° C. and keeping the temperature for 10-120 minutes after melting; S3: After the glass melt is uniform, the temperature is lowered to the melting temperature of 100-200°C and clarified for 15-60 minutes to obtain clarified glass melt; S4: pouring the clarified glass melt into a mold preheated to 350-550° C. for casting, and then cooling naturally to form glass; S5: subjecting the glass to a constant temperature precision annealing treatment to obtain the ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass. The annealing conditions are: an annealing temperature of 450-700°C and an annealing time of 3-30 hours.
6. The preparation method according to claim 5, characterized in that: The B2O3 component is introduced by boron oxide or boric acid; the SiO2 raw material is directly introduced by SiO2 raw material; and the Gd2O3 and CeO2 rare earth compounds are introduced in the form of corresponding oxides, fluorides, carbonates or nitrates; Al2O3 or Lu2O3 replacing Gd2O3 can also be introduced in the form of corresponding oxides, fluorides, hydroxides, carbonates or nitrates; the purity of all raw materials is required to be analytical grade or above.
7. The preparation method according to claim 6, characterized in that: B2O3 components through 10 B2O3 is introduced, while Gd2O3 component is introduced through 155 Gd2O3 and / or 157 Gd2O3 is introduced.
8. The preparation method according to claim 6, characterized in that: The working atmosphere during the preparation process is air atmosphere.
9. The use of ultra-high concentration cerium ions to activate Gd2O3-rich borosilicate scintillating glass according to any one of claims 1 to 4, characterized in that: The ultra-high concentration cerium ion activated Gd2O3-rich borosilicate scintillating glass is used to directly make a scintillating screen or a scintillating array, or is drawn into an optical fiber to make an optical fiber panel.
10. The use of ultra-high concentration cerium ions to activate Gd2O3-rich borosilicate scintillating glass according to any one of claims 1 to 4, characterized in that: The ultra-high concentration cerium ion-activated Gd2O3-rich borosilicate scintillating glass is used for nuclear radiation detection, high-energy physics experiments, X-ray medical imaging, neutron detection, industrial online detection and national security monitoring.
Citation Information
Patent Citations
Gd2O3-rich borogermanate scintillation glass, and preparation method and application thereof
CN102826753A
Gadolinium borosilicate scintillating glass and preparation method thereof
CN103693847A
Method for preparing Ce<3+>-activated scintillation glass in air atmosphere
CN104058578A
Colorless transparent cerium-activated borosilicate scintillation glass and preparation method thereof
CN108249757A
Cited By
Ce < 3 + >-doped silicon-boron-gadolinium scintillation glass as well as preparation method and application thereof
CN119977326A
